Symbols SYMBOLS AND MEANING INTERPRETATION IN THE “SIMPLY AUTHENTIC” VERSION OF THE CLAS MILD LIMITED EDITION ON YOUTUBE - Intan Nabila (TEXTURA, 2021)
ABSTRACTClasMild is a cigarette product that has a large market share in Indonesia, especially teenage consumers, many of them want cigarette products with low nicotine levels and attractive packaging without reducing the sense of enjoyment, that is the impression that ClasMild products want to highlight so that it becomes an icon of mild cigarettes in Indonesia. Unlike other cigarette advertisements that are deliberately made to be easily understood, the ClasMild ads is almost always display ads that are heavy to understand. This is the custom of ClasMild which has become a tradition, namely advertising in an abstract way. Therefore, the writer decided to interpret the ClasMildLimited Edition ad to find out the interpretation of the meaning of the ad. The formulation of the problem is how the symbol and meaning in the ClasMildLimited Edition ad on YouTube? With the aim of that is to find out how the semiotics of the symbols and meanings contained in the ClasMildLimited Edition ad on YouTube. Semiotics is trying to find signs that have meaning and know sign systems such as language, motion, music, pictures and so forth. Advertising is a means to convey information to the public. This research uses the methoddescriptive qualitative research. This research also concludes that the message conveyed in the advertisement is very abstract, even everyone can interpret the meaning differently (although it is still a concept). In this case it is also known that an advertising creative can make an advertisement escape from the applicable regulations while still being able to convey its message in its entirety. In addition, it was also stated that cigarette advertisement shows on television tend to show positive stories behind cigarettes that are actually negative.Keywords: Clas Mild, Simply Authentic, Semiotics, Advertising.